Kemampuan Menulis Melalui Show Not Tell Dalam Pendekatan Quantum Learning (Studi pada Madrasah Ibtidaiyah Kartoharjo Madiun) - Elen Inderasari (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2016)
This research serves an analysis for depicting: 1) the writing skill onexperiences can be developed through quantum learning approach for thestudents of fifth grade, Madrasah Ibtidaiyah, Kartoharjo, Madiun, 2) theimpacts of the implementation of quantum learning approach for thestudents of fifth grade, Islamic State Elementary School, Kartoharjo,Municipality of Madiun, 3) the efforts of teachers in developing students’writing skill on experiences in learning Bahasa Indonesia. This researchmakes use of Classroom Action Research under the collaboration of theresearcher, the teachers and the students. The analysis brings aboutconclusions that quantum learning approach has a significant influence onthe development of students’ writing skill and learning activity for thestudents of fifth grade of State Elementary School 03 Kanigoro, Kartoharjo,Municipality of Madiun. The reflection through indicators shows that: 1)students make development in their learning activity, 2) under quantumlearning approach, teachers are capable of generating students’ learningmotivation, 3) teachers are comfortable in implementing quantum learningapproach, 4) teachers are capable of managing the class well, and 5) studentsgrades up writing skill scores through report, by 65.2 in pretest, 71.9 in testand 75.6 in posttest in average.